Online repository for Ateneo De Manila High School Educational Media Center - Coballes, Brian Aljer B.
A unique characteristic of knowledge is that it allows multiple consumptions. Sharing knowledge and information does not diminish the utility of the original, thus it can multiply value creation and can be shared among different people (Asian Productivity Organization). Converting tacit knowledge from individuals and converting them into group explicit knowledge is essential in organizational learning. This knowledge is deposited and stored in a repository system for effective and efficient retrieval. Through the company's intranet, this repository accumulates information and allows access to wide number of users (Asian Productivity Organization). The project dealt with managing explicit knowledge and promoting organizational learning through a centralized repository system. The project deployed an open-source digital repository system in the Educational Media Center of Ateneo de Manila High School. The department is composed of two (2) sub-departments namely, the library which handles print and electronic resources and the Instructional Technology Center (ITC) which is in-charge of providing non-print resources to its clientele. Through the rise of popularity of using Information and Communication Technology (ICT) in the field of education, the department is making use of the latest technology to reach the most number of faculty and students. The project installed a centralized online digital repository system in a form of a website that is linked to the existing website of the department. The system provides a venue for preserving digital instructional materials uploaded to the repository. The site is deployed on its own file server that is being run by an open-source operating system. The website is integrated with the existing website of the department as well as its social networking site to promote the online repository. Because the website is accessible online, authorized users can access the resources in the repository system wherever they are and anytime they want.